HiMotion: a new research resource for the study of behavior, cognition, and emotion - Gamboa, Hugo; Silva, Hugo; Fred, Ana (Multimedia tools and applications, 2014)
The HiMotion research project was designed to create a multimodal database and several support tools for the study of human behavior, cognition and emotion, in the context of computer-based tasks designed to elicit cognitive load and specialized affective responses. The database includes both human-computer interaction (HCI) and psychophysiological data, collected through an experimental setup that we devised for synchronized recording of keyboard, mouse, and central/ peripheral nervous system measurements. Currently we provide a battery of five different cognitive tasks, and a video bank for affective elicitation, together with a set of introductory and self-reporting screens. We have conducted two experiments, one involving a population of 27 subjects, which followed the cognitive tasks protocol, and another involving a population of 20 subjects, which followed the video bank visualization protocol. We provide an overview of several studies that have used the HiMotion database to test multiple hypothesis in the behavioral and affective domains, highlighting the usefulness of our contribution.